Current Trends in the Surgical Treatment of Open-Book Pelvic Ring Injuries: An International Survey Among Experienced Trauma Surgeons. (February 2019) - Moed, Berton R.; Barla, Jorge; Israel, Heidi A.; Tovar, Shandher; Joeris, Alexander
Abstract : Introduction: In the open-book, rotationally unstable (OTA/AO type 61-B1.1) pelvic ring injury, the posterior sacroiliac complex is believed to remain intact. Therefore, anterior ring stabilization alone has been the standard treatment recommendation. However, treatment failures using this method have caused a reconsideration of this management strategy. Anterior plus posterior fixation is the main alternative. In the absence of any specific new guidelines, the choice of treatment currently relies on the preference of the treating surgeon. The objective of this survey was to determine the relative use of anterior plus posterior fixation, as opposed to the standard anterior fixation alone, for the treatment of open-book pelvic ring injuries. Methods: An international group of 176 practicing trauma surgeons experienced in pelvic ring fracture fixation participated in an AO Foundation survey asking for their preferred standard surgical fixation (anterior alone or anterior plus posterior combined) for OTA/AO type 61-B1.1 open-book pelvic fractures. Results: Anterior plate fixation alone (group 1) was preferred by 56% of the survey participants, and combined anterior plus posterior fixation (group 2) was preferred by 44%. Statistical analysis revealed that group 1 participants were significantly older than group 2 participants ( P = 0.03) and had more years of surgical experience ( P = 0.02). Conclusions: Concern regarding the inadequacy of anterior fixation alone has led many surgeons, especially those more recently in practice, to add posterior fixation, despite limited data to determine its indications. No doubt the OTA/AO type B 1.1 pelvic ring disruption actually represents a wide spectrum of injury. Further study is needed to determine the best fixation method. Abstract : Supplemental Digital Content is Available in the Text.